Monoclonal Antibody based Therapy against Cancer - Agrawal, Rashmi; Shankar, Srishti (Eastern Journal of Medical Sciences, 2024)
Cancer, as the most lethal illness, is characterized by the uncontrolled growth of cells that can be somewhat treated in the present day. Immunotherapy has been utilized to treat cancer as it has specificity against cancer cells. Apart from chemotherapy, monoclonal antibody (mAb) therapy has shown advanced effects in the treatment of cancer. mAb therapy is one of the recent developments that destroy tumor cells through different mechanisms such as antibody-dependent cellular cytotoxicity, complement-dependent cytotoxicity, antibody-dependent cellular phagocytosis, or blocking signaling pathways. This review gives a brief outline of the types, efficiency of action, challenges, and future perspectives of mAb therapy.